Spatial simulation of Claviceps gigantea (Fuentes, of the Isla, Ullstrup and Rodriguez) in the State of Mexico - Lara Díaz, Ana Verónica; Ramírez Dávila, José Francisco; Maldonado Zamora, Fátima Iraís; Figueroa Figueroa, Dulce Karen; Acosta Guadarrama, Agustín David; Rivera Martínez, Roberto; Némiga, Xanat Antonio (Revista Mexicana de Ciencias Agrícolas, 2018)
The cultivation of corn in Mexico is one of the most important highlighting the High Valleys of Mexico, in this region the main problem of cultivation are diseases, mainly those that cause ear rot which decreases yield and represents large economic losses. One of these diseases is caused by the fungus Claviceps gigantea which is commonly known as horsetooth. This disease can invade the whole cob, preventing the formation of grain. In recent years, climatic conditions have favored the proliferation of this fungus in farms cultivated with corn Zea mays L. The present work was carried out in plots of one hectare of five municipalities of the State of Mexico, with the natural incidence of the fungus during three growing cycles (2013-2015) using geostatistical techniques and performing the conditioned and unconditioned simulation process to predict the spatial behavior of the disease over time. The results show that the simulation techniques used to predict the behavior of Claviceps gigantea are an effective tool to prevent the infestations produced by this fungus. This type of study aims to help the development of integrated management programs.
Keywords: corn, fungal disease, horse tooth, simulation